Evaluation of burnout performance of biomass wastes in a rocket-engine-based incinerator. (1st March 2015) - Son, Jin Woo; Sohn, Chae Hoon
Highlights: Burning performance of biomass wastes is evaluated numerically in the RBI chamber. The correlation is found between burnout ratio and a similarity variable. A single-valued parameter is provided for prediction of burning rate of biomass. Burning performance in the RBI is still high in burning of biomass wastes. Abstract: Burning performance of biomass wastes has been evaluated numerically in the chamber of a rocket-engine-based incinerator (RBI), which was suggested as a device of a solid-particle incinerator for the purposes of both high-performance burnout and mobility. Especially, the incineration is fitted better for disposal of hazardous animal carcass than its burial. For high burning performance, the chamber of a RBI has the shape of a rocket combustor and in-chamber swirl flow is formed by peripheral injectors. First, the chamber is optimized to maximize burning rate because biomass has broader ranges of elements content and thermal properties than coal, leading to degraded burning of biomass. The optimal ratio of chamber diameter to length and the optimal deflection angle of the injector are found. Next, four kinds of fuels or wastes are burned and their burning rates are evaluated with the optimal chamber. Wood has the highest burning rate of them, and solid wastes and animal carcass have lower one than coal, but their rates are still absolutely high in this chamber. Burning rates of solid wastes and animal carcass decrease abruptly as particle diameter increases over 1 mm. The proposed chamber with the RBI concept has been verified to attain higher burnout performance of biomass wastes than a conventional incinerator by a factor of 5. And, pressure and burnout ratio are increased additionally when the 2nd chamber is attached downstream.